Making public transport the choice mode - Tan, Rachel Li Wen (2016)
As Singapore’s population approaches 6.9 million by 2030, new challenges arise for the transportation system in meeting the increasing demand for travel. As such, the aim of this study is to determine the factors that would sustain or even increase the current ridership of public trains and buses in Singapore. It is crucial to focus on specific factors that commuters view as important when taking the train, and whether the existing train services are up to their expectations. This study is a joint collaboration with the Public Transport Council who might find some of the data and factors useful in future larger scaled studies. The general methodology of the study includes literature review, designing and conducting of survey, data analysis and discussion of results. Surveys for bus and train services were conducted separately, with a sample size of 138 each based on a confidence interval of 90% and marginal error of 7%. This report focuses on public train services, which refers to the Mass Rapid Transit (MRT) network in particular. Bus services are analysed in a separate report by the authors’ project partner. 6 categories of factors were included in the study; Accessibility, Reliability, Comfort, Information, Safety and Security and Customer Care. Respondents were asked to rate on a Likert scale of 1 to 7, how important each factor was to them. The data analysis methods used are descriptive statistics (mean and ranking), one way ANOVA test and frequency analysis. Using the means calculated for each factor, the top 3 factors were determined based on the top 3 overall means. It was discovered that the most important factor with the highest mean was “Staff have sufficient information on service disruption”, followed by “Temperature and ventilation levels in train cabin are good” and “Sufficient time for passengers to board the train”. One way ANOVA test was used to investigate if there were significant differences in the importance ratings of the top 3 factors. For a confidence interval of 95%, the top 3 factors were not significantly different. Frequency analysis was done on the top 3 factors to observe how differently respondents rated based on their frequency of taking the train. It was found that heavy users (more than 3 days a week) rated with more extremity than non-heavy users. It is encouraging to note that local transport authorities and train operators’ recent efforts and initiatives are in line with the needs of commuters as discovered in this study, and should be continued to gain trust and loyalty amongst Singaporeans.